Urtica dioica dichloromethane extract induce apoptosis from intrinsic pathway on human prostate cancer cells (PC3) - Mohammadi, A; Mansoori, B; Aghapour, M; Baradaran, B (Cellular and Molecular Biology, 2016)
Prostate cancer is considered as the major cause of death among men around the world. There are a number of medicinal plants triggering apoptosis response in cancer cells, thus have a therapeutic potential. Therefore, further studies to characterize beneficial properties of these plants in order to introduce novel anti-cancer drugs are the interest of recent researches on the alternative medicine. On the other hand, due to traditional uses and availability of Urtica dioica extract, we decided to evaluate the efficacy of this medicinal herb on pc3 prostate cancer cell line. In the present study the cytotoxic effects of Urtica dioica extract were assessed by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay and trypan blue viability dye. Then, DNA fragmentation and terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay were exploited to measure cell death and apoptosis stage. The expression levels of caspase 3, caspase 9 and Bcl-2 genes were quantified by Real-Time PCR. Finally, Cell cycle was analyzed by flow cytometry. MTT assay showed that dichloromethanolic extract of Urtica dioica significantly inhibited the cell growth. According to the DNA fragmentation and TUNEL assay results, the herbal extract was able to induce apoptosis in prostate cancer cells. Our findings also demonstrated that the plant extract substantially increases the caspase 3 and 9 mRNA expression, while decreases Bcl-2. Cell cycle arrest was occurred in G2 stage, due to the results of flow cytometry. These results indicate that dichloromethanolic extract of Urtica dioica can successfully induce apoptosis in PC3 cells. Therefore, it could be used as a novel therapeutic candidate for prostate tumor treatment.